Five species of the family Odiidae (Crustacea: Amphipoda) collected from Japan, with descriptions of a new genus and four new species - Ariyama, Hiroyuki (Zootaxa, 2021)
Five species of the family Odiidae (Amphipoda), including four new species, are recorded from Japan: Metodius cyanomaculatus sp. nov.; M. leucomaculatus sp. nov.; Postodius albifacies sp. nov.; P. sanguineus sp. nov.; and Antarctodius japonicus Ariyama, 2011. Morphological characters and coloration of these species are described in detail. Metodius gen. nov. is established for the two new species and is characterized by the very short and bare palp of the maxilla 1 and the large gnathopod 2 propodus. Keys to the odiid genera and the Postodius species in the world are provided. The genera can be distinguished from one another by the shapes of maxilla 1, maxilliped, pereopod 7, and telson. The Postodius species differs in the shapes of gnathopod 2, and pereopods 3, 7. Female of A. japonicus is firstly recorded. In this species, the presence of an accessory flagellum and a gill on the coxa 7 is confirmed.